The Effect Social Influence on the Interest in Implementation A Regional Financial Management Information System (SIPKD) in Padang City Goverment - Melda Hayati; Febryandhie Ananda (Future Science, 2021)
This study aims to examine the effect of a social influence on the interest in implementation a regional financial management information system (SIPKD) in Padang PEMKOT. This study is all regional work units that use the regional financial management information system and is also based on the results of the 80 respondents who used the regional financial manager information system who has worked in the Padang City Hall government. In addition, this study uses research respondents who are distributed directly and uses simple linear regression techniques that aim to test research data with the help of SPSS 25. The study uses the social influence of independent variables and one dependent variable, namely: interest in implementation regional financial management information system. The results showed that social influence has a significant influence on the interest in implementation a regional financial management information system.